Transition Metal Dissolution and Degradation in NMC811-Graphite Electrochemical Cells. Issue 6 (21st June 2021) - Ruff, Zachary; Xu, Chao; Grey, Clare P.
Abstract : Nickel-rich lithium nickel-manganese-cobalt oxide cathodes, in particular Li(Ni0.8 Mn0.1 Co0.1 )O2 (NMC811), are currently being commercialized as next generation cathode materials, due to their increased capacities compared to current materials. Unfortunately, the higher nickel content has been shown to accelerate cell degradation and a better understanding is needed to maximize cell lifetimes. NMC811/graphite cells were tested under stressed conditions (elevated temperature and cell voltages) to accelerate degradation focusing on transition metal (TM) dissolution from the cathode. Increasing the cell temperature, upper cut-off voltage (UCV) and number of cycles all accelerated capacity fade and diffraction studies showed that under stressed conditions, additional degradation mechanisms beyond lithium loss to the SEI are present. Significant TM dissolution and subsequent deposition on the graphite anode is seen, particularly at stressed conditions. The concentration of TMs in the electrolyte remained invariant with cycling conditions, presumably reflecting the limited solubility of these ions and emphasizing the role that TM deposition on the anode plays in continuing to drive dissolution. Significant deposits of metals from the cell casings and current collectors were also detected at all cycling conditions, indicating that corrosion and metal leaching can be as important as TM dissolution from the active material in some cell formats.